Diagnostic performance of FibroScan in liver fibrosis staging in a tertiary care hospital of Nepal - Prasad, V.Natraj (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: Liver fibrosis is the excessive accumulation of extracellular matrix proteins resulting from chronic liver injury caused by viral hepatitis, non-alcoholic fatty liver disease, or alcoholism. If undiagnosed, it can progress to cirrhosis, liver failure, and hepatocellular carcinoma, emphasizing the need for early detection. Although liver biopsy was once the gold standard for fibrosis assessment, it is invasive and prone to complications and sampling errors. To overcome these limitations, non-invasive imaging methods such as FibroScan have been developed. This research aimed to study the diagnostic performance of FibroScan in liver fibrosis staging in a tertiary care hospital of Nepal. Methods: A hospital-based cross-sectional study was conducted among 60 adult patients with chronic liver disease. All participants underwent liver stiffness measurement using FibroScan and liver biopsy. Fibrosis was staged according to the METAVIR scoring system. Cut-off values of ≥7.1 kPa and ≥9.5 kPa were used to define significant (≥F2) and advanced fibrosis (≥F3), respectively. Diagnostic performance metrics including sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), accuracy, and area under the ROC curve (AUC) were calculated. Mean liver stiffness was compared across fibrosis stages. Results: Histopathology revealed F0–F1 in 30%, F2 in 20%, F3 in 23.3%, and F4 in 26.7% of patients. For significant fibrosis (≥F2), elastography showed sensitivity 88.6%, specificity 89.2%, PPV 81.6%, NPV 93.5%, accuracy 89%, and AUC 0.93. For advanced fibrosis (≥F3), sensitivity was 90%, specificity 83.3%, PPV 84.4%, NPV 89.3%, accuracy 86.7%, and AUC 0.91. Mean liver stiffness increased significantly with fibrosis stage (F0–F1: 5.8 ± 1.2 kPa to F4: 12.5 ± 1.5 kPa; P = 0.01). Conclusions: FibroScan is a reliable non-invasive tool for detecting significant and advanced liver fibrosis, demonstrating high diagnostic accuracy and good correlation with histopathological findings.